Coronavirus disease 2019 (COVID‐19): strengthening our resolve to achieve universal palliative care - Rosa, William E. (Int Nurs Rev, 2020)
In this paper, we strongly advocate for universal palliative care access during the COVID‐19 pandemic. The delivery of universal palliative care services has been called for by leading global health organizations and experts. Nurses are critical to realizing this goal. COVID‐19 diagnoses and fatalities continue to rise, underscoring the importance of palliative care, particularly in the context of scant resources. To inform the writing of this paper, we undertook a review of the COVID‐19 and palliative care literature and drew on our experiences. It is very clear that investment in nurses is needed to ensure appropriate palliative care services now and into the future. Avoiding futile interventions and alleviating suffering is an ethical imperative for nurses regardless of the setting. Multi‐level practices and policies to foster the delivery of safe, high‐quality palliative care for all are urgently needed.